A Saint Louis encephalitis and Rocio virus serosurvey in Brazilian horses - Jaqueline Raymondi Silva; Marilia Farignoli Romeiro; William Marciel de Souza; Thiago Demarchi Munhoz; Gustavo Puía Borges; Otavio Augusto Brioschi Soares; Carlos Henrique Coelho de Campos; Rosângela Zacarias Machado; Maria Luana Cristiny Rodrigues Silva; Joice Lara Maia Faria; Juliana Helena Chávez; Luiz Tadeu Moraes Figueiredo (Revista da Sociedade Brasileira de Medicina Tropical, 2014)
Introduction Arboviruses are an important public health problem in Brazil, in especially flaviviruses, including the Saint Louis encephalitis virus (SLEV) and the Rocio virus (ROCV), are especially problematic. These viruses are transmitted to humans or other vertebrates through arthropod bites and may cause diseases with clinical manifestations that range from asymptomatic infection, viral hemorrhagic fever to encephalitis. Methods A serological survey of horses from various regions of Brazil using an enzyme-linked immunosorbent assay (ELISA) with recombinant SLEV domain III peptides and ROCV E protein as antigens. Results Overall, 415 (55.1%) of the 753 horses that were screened were seropositive for flavivirus and, among them, monotypic reactions were observed to SLEV in 93 (12.3%) and to ROCV in 46 (6.1%). These results suggested that these viruses, or other closely related viruses, are infecting horses in Brazil. However, none of the studied horses presented central nervous system infection symptoms. Conclusions Our results suggest that SLEV and ROCV previously circulated among horses in northeast, west-central and southeast Brazil.